1991
DOI: 10.1136/adc.66.10.1191
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive hypoparathyroidism with renal insufficiency and developmental delay.

Abstract: Four children (two boys and two girls) with hypoparathyroidism, renal insufficiency, and developmental delay are described. They were the products of consanguineous marriages in three related Asian families presenting over a six year period. AU figure). He was the first child of Asian parents who were first cousins. He became lethargic on the ninth day of life and investigations showed evidence of a metabolic acidosis (pH 7-18, base excess -17 mmol/l), with hypocalcaemia (1-32 mmol/l), and hyponatraemia (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
2
17
0
2
Order By: Relevance
“…A diagnosis has not yet been established. It is possible that MP has a more severe and extensive form of the syndrome described in Saudi, Kuwaiti, and Asian children with hypoparathyroidism [Richardson and Kirk, 1990;Sanjad et al, 1991;Shaw et al, 1991]. On the other hand, his clinical findings are remarkably similar to those found in patients with mitochondrial diseases.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…A diagnosis has not yet been established. It is possible that MP has a more severe and extensive form of the syndrome described in Saudi, Kuwaiti, and Asian children with hypoparathyroidism [Richardson and Kirk, 1990;Sanjad et al, 1991;Shaw et al, 1991]. On the other hand, his clinical findings are remarkably similar to those found in patients with mitochondrial diseases.…”
Section: Discussionsupporting
confidence: 49%
“…Shaw et al have described another autosomal recessive form of congenital hypoparathyroidism in 4 children from an Asian kindred [Shaw et al, 1991]. This phenotype also included renal tubular acidosis, progressive renal insufficiency, severe developmental delay, failure to thrive of postnatal onset, and sensorineural deafness.…”
Section: Discussionmentioning
confidence: 97%
“…Some of the patients developed renal insufficiency early in life. The autosomal recessive form of hypoparathyroidism with sensorineural deafness and renal tubular dysfunction was detected in two families (8,9). However, the family described in this report showed normal renal imaging and normal renal tubular function.…”
Section: Discussionmentioning
confidence: 38%
“…In our patient, no predisposing factors were found except for HDR syndrome. Although cerebral infarction was not reported in patients with partial deletion of 10p [Kato et al, 1996] or in those with idiopathic hypoparathyroidism, one of the two children with HDR syndrome described by Shaw et al [1991] had several small foci of lowdensity parenchyma in the left hemisphere that had the appearance of infarcts on cranial CT. Recurrent cerebral infarctions may be one of the clinical features in HDR syndrome.…”
Section: Discussionmentioning
confidence: 92%
“…Yumita et al [1986] described a male with hypoparathyroidism, progressive sensorineural deafness, and aplasia or hypoplasia of the right kidney. Shaw et al [1991] reported on two children with hypoparathyroidism, sensorineural deafness, and renal insufficiency who were also severely developmentally delayed and showed a failure to thrive, dying at ages 7 months and 14 months, respectively. Bilous et al [1992] described two brothers and two daughters of one of the brothers with hypoparathyroidism, sensorineural deafness, and renal dysplasia.…”
Section: Clinical Reportmentioning
confidence: 97%